An analysis of the recent restructuring of network assets by the largest international mobile operators. Issue 3 (9th May 2016) - Curwen, Peter; Whalley, Jason
Abstract : Purpose: This paper aims to examine the extent to which the largest international mobile operators are restructuring their network assets to adapt to a rapidly changing environment. Design/methodology/approach: A number of original databases have been constructed that identify the relevant operators, both current and over an eight-year period, where they operate on a regional basis, their purchases and sales of network assets during those eight years and their unfulfilled aspirations to buy and sell network assets. Findings: It is reasonably evident that operators have clear strategic objectives when deciding where and when to expand their empires, and that they have a clear preference for regional clustering of assets. However, the paucity of desirable networks for sale means that asset buying has to be opportunistic and that operators come up against problems such as an unwelcoming government or a corrupt regime which makes operators come to regret their initial enthusiasm. In recent years, the emphasis has switched from building empires consisting solely of mobile networks towards the development of multi-play capabilities within a limited number of countries. Practical implications: Databases are compiled by many organisations for their own purposes. They are usually difficult to interpret because of a lack of explanatory footnotes and often contain mistakes. The authors compile their own unique databases and, therefore, have a better understanding of the reasons why strategic decisions are made that affect the buying and selling of international assets. Originality/value: The existence of these databases mean that the authors' work is highly original, even though it is, of necessity, based upon public domain sources.